2019
DOI: 10.1080/02656736.2019.1612103
|View full text |Cite
|
Sign up to set email alerts
|

The impact of whole-body hyperthermia interventions on mood and depression – are we ready for recommendations for clinical application?

Abstract: Objective: To systematically summarize the findings from research studies examining the effects of whole-body hyperthermia (WBH) interventions on mood and symptoms of depression. Methods: Systematic literature search of online and offline databases (e.g., Pubmed, Web of Knowledge, Cochrane, academic libraries). Risk of bias assessment and secondary analysis of effect sizes. Study selection: Clinical studies with a pre/post-intervention design and outcome measures for mood and depression as accepted in the S-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…They found that the WBH group had a significant reduction in Hamilton Depression Rating Scale scores across the 6‐week post intervention study period compared to sham 4 . Furthermore, a systematic review examining the utility of WBH for mood and depressive symptoms was carried out in 2019 5 . Their analysis showed that in 6/7 included studies, a statistically significant reduction in mood and depressive symptoms was found independent of sample size, total number and frequency of treatment sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the WBH group had a significant reduction in Hamilton Depression Rating Scale scores across the 6‐week post intervention study period compared to sham 4 . Furthermore, a systematic review examining the utility of WBH for mood and depressive symptoms was carried out in 2019 5 . Their analysis showed that in 6/7 included studies, a statistically significant reduction in mood and depressive symptoms was found independent of sample size, total number and frequency of treatment sessions.…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, a systematic review examining the utility of WBH for mood and depressive symptoms was carried out in 2019. 5 Their analysis showed that in 6/7 included studies, a statistically significant reduction in mood and depressive symptoms was found independent of sample size, total number and frequency of treatment sessions.…”
Section: Clinical Curiositymentioning
confidence: 99%
“…Außerdem kommt es zu einer passageren Stoffwechselsteigerung, auch in bradytrophen Geweben, sowie zu einer Relaxation der quergestreiften und sogar der glatten Muskulatur 7 . Nachweislich wirkt die mGKHT auch antidepressiv 2 . Während eines Aufenthalts werden 2–3 mGKHTs pro Patient geplant, wenn keine Kontraindikationen oder eine ausgeprägte Hitzeunverträglichkeit bestehen.…”
Section: Behandlungsmethoden Des Kfnunclassified
“…Außerdem kommt es zu einer passageren Stoffwechselsteigerung, auch in bradytrophen Geweben, sowie zu einer Relaxation der quergestreiften und sogar der glatten Muskulatur [7]. Nachweislich wirkt die mGKHT auch antidepressiv [2] Das mögen keine "großen Sprünge" sein, aber bei der Selbsteinschätzung der Lebensqualität und des Gesundheitszustands sind eindeutige und nachhaltige Besserungstendenzen durch eine einmalige 10-tägige naturheilkundliche Komplexbehandlung nachweisbar. Eine Wiederholung der stationären naturheilkundlichen Komplexbehandlung, z.…”
unclassified
“…This projected shift towards a sub-nocturnal lifestyle could be associated with the limbic system, which drives human behavior to operate in a "comfort zone" [141,142,154]. A higher Tev is also associated with sub-optimal mood, mental functions, and motor skill and physical performances, which compromise occupational health and productivity, and sports performance [85,194,[236][237][238][239]. An example of circadian-related adaptation to heat in current time is in the planning of the 2020 Tokyo Olympic Games, which was anticipated to have warmer than usual summer climate (The event was postponed to 2021 due to the COVID-19 pandemic).…”
Section: Circadian Shift To Sub-nocturnal Lifestylementioning
confidence: 99%